Localish Program: Instilling Local Wisdom Values and Enhancing English Speaking Skills of Elementary School-Age Children - Wida Mulyanti; Lystiana Nurhayat Hakim; Setyo Wati (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The Localish Program is a community service program in the form of teaching English that focuses on improving speaking skills and providing local wisdom values through storytelling activities for elementary school-age children who live in Kampung Cantilan, Sukarame Village, Tasikmalaya Regency. This program is a follow-up program from the previous community service program, namely empowering English book libraries and teaching English which focuses on increasing vocabulary. The method used is the practice of community development adapted from Vincent (2009) starting from forming a team, formulating goals, determining target community, analyzing the needs of the target community, prioritizing problem solutions, preparing, implementing, reviewing and evaluating, and the last is determining new needs and target community. While the steps used in the learning process are: orientation, training, feedback, and continuation. Pre-test and post-test were carried out on seventeen participants at the beginning and end of the program. From the results of these tests, it can be interpreted that the English-speaking skills of elementary school age children in Kampung Cantilan have increased after participating in this program. Meanwhile, the results of the interviews proved that this program contributed in increasing children's understanding of local wisdom values.